Systematic position of two Athamanthia Zhdanko, 1983 (Lepidoptera, Lycaenidae) taxa from the Iranian Plateau - Krupitsky, Anatoly V.; Pljushtch, Igor G.; Skrylnik, Yuriy Ye. (Zootaxa, 2017)
In the present paper we refine the systematic position of an unclear lycaenine taxon povolnyi Howarth & Povolny, 1976 previously known only from the holotype male. Based on the appearance and morphology of the male genitalia we recognize it as a subspecies of Athamanthia balucha (Howarth & Povolny 1976)—A. b. povolnyi (Howarth & Povolny, 1976), comb. nov. Morphology of the subspecies is redescribed, female is described and illustrated for the first time, and distribution data are added taking into consideration recent findings in Bamyan province of Afghanistan. Taxon athamantides Eckweiler & ten Hagen, 2001 from Central and Southeast Iran is also treated as a subspecies of A. balucha—A. b. athamantides (Eckweiler & ten Hagen, 2001), comb. nov.—based on the similarity of the male genitalia and the wing pattern with A. balucha.